Pemanfaatan Limbah Abu Batok Kelapa dan Kapur Hidrolis sebagai Bahan Substitusi Semen pada Paving Block - Nura Diana, Anita Intan; Zainah, Nor (MEDIA KOMUNIKASI TEKNIK SIPIL, 2022)
Sumenep has a large amount of coconut shell ash waste from the briquette industry and a considerable potential for producing limestone (hydraulic lime). The development of road transportation infrastructure as a regional development in Indonesia using paving blocks has resulted in increased demand for cement. Utilization of waste and the potential of local materials must be endeavored by users, both of which have the same content as cement. The research method used an experimental method by replacing the cement with coconut shell ash waste and hydraulic lime, each of 0%, 5%, 10%, 15%, 20%. data analysis techniques using multiple linear regression method with the help of SPSS software. The results of the study with the help of SPSS software showed that the addition of variations in coconut shell ash waste and hydraulic lime did not have a simultaneous effect on the compressive strength and absorption of water. Laboratory research results show a maximum compressive strength of 18.616 Mpa and an average water absorption of 10.751% with the addition of each variation of 5% coconut shell ash waste and hydraulic lime, based on SNI -03-0691-1996 compressive strength including quality classification B, while absorption does not meet the requirements for absorption quality classification.